PENGARUH PROFITABILITAS DAN RISIKO KREDIT TERHADAP CAPITAL ADEQUACY RATIO DAN HARGA SAHAM - Satrigraha, Ni Putu Tika Andriani; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Investment decision by investor can be influence by stock price of the firm. Firm must be pay attention in financial management to keep stock price in high level that can reassure the investor to invest capitals in firm. This study purposed to detect relation between profitability and credit risk to capital adequacy ratio and also stock price at banking sector with fifteen firms as samples from twenty nine firms in populations that used purposive sampling as sampling technique. Path analysis used to analyze this observation. The result found that profitability has no significant effect to capital adequacy ratio but positive significant to stock price; credit risk related negative significant to capital adequacy ratio but has no significant influence to stock price and profitability; at last found that capital adequacy ratio has no significant impact to stock price. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";}